Role of Dynamic Contrast Enhanced Magnetic Resonance Imaging and Mammogram in Evaluation of Breast Lesions with Pathological Correlation - K Harsha Veena; Ramakrishna Rao Baru (Asian Journal of Medical Radiological Research, 2020)
Background: To perform mammography and dynamic contrast enhanced MRI in patients with clinically suspicious breast lumps and correlating the findings with pathology in patients of positive imaging. Subjects and Methods: total of 40 patients evaluated through MRI BI-RADS lexicon (General Electric Medical Systems) at 1.5T in combination with dynamic kinetic analysis of time and signal curves for lesion characterization. Results: The mean age was 44 years, maximum of patients (n=22) belongs to age group of 41-60 years (52.5%). Five lesions showed dark internal septations, as benign. 11 lesions (33.5%) showed heterogenous enhancement, as malignant. Early rim enhancement is observed in 3 lesions (9%). Out of which two of them were proven to be malignant and one lesion was an infective abscess. Invasive Duct Cell Carcinoma was the common histology in the malignant lesions, observed in 13 out of 18 (72.2%). Fibroadenoma was the common benign breast lesion, observed in 8 out of 19 (42.1%). In 4 post operative patients, 2 (50%) were post operative fibrosis, 1 (25%) was recurrence and 1 (25%) was post operative collection. In 18 malignant lesions, 11 patients (61.1%) had skin retraction, 10 patients (55.5%) had skin thickening, 9 patients (50%) had axillary lymphadenopathy, 2 patients (11.1%) had nipple retraction, and one patient (5.6%) had pectoralis involvement. In our study, MR imaging alone has Sensitivity of 88.8%, specificity of 86.3%, PPV of 84.2%, and NPV of 90.4% with Accuracy 87.5%. Conclusion : The dynamic contrast enhanced MRI is important tool to evaluate the postoperative breast in differentiating between benign postoperative changes. By combining kinetic analysis with morphological analysis it add benefit to categorise the breast lesions into benign and malignant with increased confidence levels. CE-MRI with both morphology and kinetic curve assessment has a Sensitivity of 94.5%, Specificity of 100% with Accuracy of 97.5%.